Fully 3D‐Printed, Ultrathin Capacitors via Multi‐Material Microsputtering. Issue 8 (3rd April 2022) - Kornbluth, Yosef S.; Parameswaran, Lalitha; Mathews, Richard; Racz, Livia M.; Velásquez‐García, Luis F.
Abstract: This study reports the first fully additively manufactured capacitors as a proof‐of‐concept demonstration of direct‐write, ultrathin‐film electronic components made via multi‐material microplasma sputtering. This is also the first demonstration of a cleanroom‐quality, multi‐material electrical device produced entirely through additive manufacturing. Ultrathin metal and dielectric films are deposited at <80 °C and atmospheric pressure conditions on a substrate using a novel, continuously fed, dual target microsputtering printhead. The conductive films are created by sputtering gold in an air atmosphere and shown to attain near‐bulk electrical resistivity. The dielectric films are created by sputtering aluminum in a gas blend of argon and air; the aluminum oxidizes in the high‐energy, high‐collisionality plasma, forming alumina nanoparticles that are deposited on the substrate. Ultra‐thin (35 nm) alumina films showed extremely high resistivity (100 GΩ‐m) and dielectric strength (6.2 GV m −1 ). Also, the frequency response of the capacitor is satisfactorily described by the universal dielectric response typically found in heterogenous dielectrics. It is hypothesized that the dielectric response is the result of the presence of condensed water in the pores of the alumina film. Abstract : This study reports the first demonstration of a cleanroom‐quality, multi‐material electrical device produced entirely via additive manufacturing, serving as an important demonstration of the potential of multi‐material microsputtering to manufacture custom electronics at low temperature (<80 °C) and atmospheric pressure conditions. The devices are ultra‐thin capacitors with gold electrodes and alumina dielectric with excellent DC and AC electrical properties.